2018
DOI: 10.1186/s13054-018-1988-y
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of antiplatelet therapy in acute respiratory distress syndrome: a meta-analysis

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is a life-threatening condition with high mortality that imposes a serious medical burden. Antiplatelet therapy is a potential strategy for preventing ARDS in patients with a high risk of developing this condition. A meta-analysis was performed to investigate whether antiplatelet therapy could reduce the incidence of newly developed ARDS and its associated mortality in high-risk patients.MethodsThe Cochrane Central Register of Controlled Trials (CENTRAL), Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Three recent meta-analyses have reported significantly increased survival in ARDS patients prescribed aspirin compared to those who were aspirin free [ [160] , [161] , [162] ]. Furthermore, the effect appear to be greater in critically ill patients and patients with ARDS-related sepsis than a wider group of patients [ 160 , 161 ].…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%
“…Three recent meta-analyses have reported significantly increased survival in ARDS patients prescribed aspirin compared to those who were aspirin free [ [160] , [161] , [162] ]. Furthermore, the effect appear to be greater in critically ill patients and patients with ARDS-related sepsis than a wider group of patients [ 160 , 161 ].…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%
“…Platelets have an increasingly recognized role in the inflammatory response, leading to the development of ARDS. The possible mechanisms by which platelets contribute to ARDS include the activation of endothelial cells by the release of pro-inflammatory mediators [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and adherence of platelets to lung capillary endothelial cells leading to the activation of attached leukocytes [ 47 ], as shown in Figure 2 .…”
Section: Mechanisms Of Platelet In Lung Inflammationmentioning
confidence: 99%
“…Both the incidence of ARDS (OR: 0.67) and the need for mechanical ventilation (OR: 0.74) were lower in the antiplatelet group [ 113 ]. On the contrary, Wang et al analyzed nine eligible studies, and found that antiplatelet therapy did not significantly decrease hospital mortality in high-risk patients, and an association with the incidence of ARDS remains unclear [ 43 ].…”
Section: Meta-analysis Of Clinical Studiesmentioning
confidence: 99%
“…A clinical benefit of statins in an emergency situation involving sepsis would require a much more immediate effect than can be produced by this mechanism. Similarly, the effect of aspirin in ARDS revealed from retrospective analysis [17] was not repeated in a prospective trial where no significant difference was found in newly developed ARDS [18].…”
Section: Metforminmentioning
confidence: 99%